The Phenomenon of Determining the Start of Ramadan between the Government and Muhammadiyah from the Perspective of Religious Science - Vina Novita; Z. Zarkasih; Rian Vebrianto (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Determining the start of Ramadan in Indonesia often creates differences between the government, through the Ministry of Religious Affairs, and Islamic organizations such as Muhammadiyah, rooted in methodological variations in understanding religious evidence and astronomical approaches. This study aims to analyze the differences in the rukyat and hisab methods from a scientific and religious perspective using a mixed-methods approach with a sequential explanatory design. The study involved 30 respondents from Nahdlatul Ulama (NU) and Muhammadiyah, who were purposively selected based on their active involvement in the organizations' religious activities. Data were obtained through a Google Form-based questionnaire and interviews, as well as field data collection through Focus Group Discussions (FGDs). Data analysis was conducted qualitatively and quantitatively using triangulation techniques to ensure validity. A reliability test using Cronbach's Alpha was conducted on a 30-item questionnaire instrument covering seven variables; a reliability coefficient of 0.89 was obtained, indicating high instrument consistency. The results showed that 90–97% of respondents demonstrated a high understanding and acceptance of the rukyat and hisab methods, with the integration of religious science and religious perspective variables achieving the highest agreement (97%). Differences in determining the start of Ramadan are not only methodological but also reflect theological, scientific, and social dynamics. The novelty of this research lies in the comprehensive integration of astronomical science and Islamic jurisprudence perspectives in examining the phenomenon of determining the Hijri calendar, which provides a new theoretical framework for the study of religious science integration in the context of the Indonesian Hijri calendar. Therefore, it is recommended to strengthen education regarding rukyat and hisab methods and increase dialogue between the government and religious organizations such as Nahdlatul Ulama (NU) and Muhammadiyah to achieve harmony amidst methodological diversity.